Impact of motion induced artifacts on automatic registration of lung tumors in Tomotherapy. Issue 8 (December 2015) - Goossens, Samuel; Descampe, Antonin; Orban de Xivry, Jonathan; Lee, John A.; Delor, Antoine; Janssens, Guillaume; Geets, Xavier
Highlights: We aimed to validate a tumor-based registration of lung tumors in Tomotherapy. We explored the effect of motion-induced MV-CT artifacts on automatic registration. Registration errors were acceptable (within 1.3 ± 1.2 mm). Only breathing period of 5 s induced more significant registration errors. This period should be avoided by applying audio guidance during MV-CT acquisition. Abstract: Purpose: Tomotherapy MV-CT acquisitions of lung tumors lead to artifacts due to breathing-related motion. This could preclude the reliability of tumor based positioning. We investigate the effect of these artifacts on automatic registration and determine conditions under which correct positioning can be achieved. Materials and methods: MV-CT and 4D-CT scans of a dynamic thorax phantom were acquired with various motion amplitudes, directions, and periods. For each acquisition, the average kV-CT image was reconstructed from the 4D-CT data and rigidly registered with the corresponding MV-CT scan in a region of interest. Different kV–MV registration strategies have been assessed. Results: All tested registration methods led to acceptable registration errors (within 1.3 ± 1.2 mm) for motion periods of 3 and 6 s, regardless of the motion amplitude, direction, and phase difference. However, a motion period of 5 s, equal to half the Tomotherapy gantry period, induced asymmetric artifacts within MV-CT and significantly degraded the registration accuracy. Conclusions: As long as the breathing period differs from 5 s, positioning based on averaged images of the tumor provides information about its daily baseline shift, and might therefore contribute to reducing margins, regardless of the registration method.